2003
DOI: 10.1177/152660280301000522
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Adhesion to Simulated Stented Surfaces

Abstract: Additional knowledge of the role of mechanical factors in stent restenosis will aid in designing stents that minimize intimal hyperplasia and restenosis. The results of this study demonstrate the importance of stent design-mediated blood flow patterns, with smaller strut spacings minimizing platelet adhesion per unit strut area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…Higher degrees of platelet aggregation have been noted in regions where instantaneous streamlines point toward the wall. One result of this behavior is that in areas where stent struts are very closely packed, and the mainstream of the flow “skims over” the top of the stagnant area in between, platelet aggregation is lowest (9). Presumably, delivery of blood-borne inflammatory cells follows similar patterns.…”
mentioning
confidence: 99%
“…Higher degrees of platelet aggregation have been noted in regions where instantaneous streamlines point toward the wall. One result of this behavior is that in areas where stent struts are very closely packed, and the mainstream of the flow “skims over” the top of the stagnant area in between, platelet aggregation is lowest (9). Presumably, delivery of blood-borne inflammatory cells follows similar patterns.…”
mentioning
confidence: 99%
“…In addition, it is not well understood how changes in local geometry affect near-wall flow. Several investigations have shown that flow in and around stent struts play a significant role in platelet binding, thrombus formation, and neointimal hyperplasia [40][41][42]. These phenomena each have an effect on remodeling behavior around the strut area and interact in a way that does not produce significant differences within these force ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Endovasküler perspektiften bakıl-dığında akut stent trombozunda, aktive olan trombositlerin "shear stress" (kan akımı) altın-da stent metal yüzeyine adezyonu ve ardından agregesyonu gerçekleşir [13]. Yani agonistle aktive edilen trombositlerin, shear stress altın-da (manyetik karıştırıcı) metal yüzeye (gümüş kaplı bakır elektrodlar) yapışması ve sonuçta elektrodlar arası artan empedansın sayısal veriye dönüştürülmesi şeklindeki çalışma prensibi, Multiplate Analyser testini endovasküler tedaviler için teoride daha doğru test yapmaktadır.…”
Section: Endovasküler Perspektife Göre Hangi Test?unclassified